A short stature allele enhances tolerance to zinc deficiency and translocation of zinc in barley - Saygili,Ibrahim (PeerJ, 2024)
Background Zinc (Zn) content is of great importance in healthy human diet, crop productivity and stress tolerance in soils with zinc deficiency. The genes used to increase yield per unit area such as semi-dwarf 1 (sdw1) is commonly considered to reduce mineral content of grain. Methods In the present study, influence of sdw1.d, a widely used allele for short plant height in barley breeding, on zinc accumulation and tolerance to zinc deficiency were investigated. A near isogenic line of sdw1.d allele, its recurrent parent Tokak 157/37 and donor parent Triumph were grown in zinc-deficient and-sufficient hydroponic cultures. Two experiments were conducted until heading stage and physiological maturity. Results In zinc-deficient conditions, sdw1.d allele increased shoot dry weight by 112.4 mg plant−1, shoot Zn concentration by 0.9 ppm, but decreased root Zn concentration by 6.6 ppm. It did not affect grain characteristics, but increased grain Zn content. In zinc-sufficient conditions, sdw1.d allele increased shoot Zn content, and decreased root Zn content. sdw1.d did not affect grain weight but increased grain Zn concentration by about 30% under zinc-sufficient conditions. The results showed that sdw1.d allele has no negative effect on tolerance to zinc deficiency, and even promotes tolerance to zinc deficiency by more Zn translocation. It was revealed that sdw1.d allele improves Zn accumulation under both zinc-deficient and zinc-sufficient condition. The sdw1.d allele could contribute to solving the problems in plant growth and development caused by zinc-deficiency via improving tolerance to zinc-deficiency. It could also provide a better Zn biofortification.
Keywords: Biofortification; Gibberellic acid; Hordeum vulgare; HvGA20ox2; Zinc; sdw1.d